Encapsulation of a Pediocin PA-1 producer Pediococcus acidilactici and its impact on enhanced survival and gut microbiota modulation - M. Mokrani; A. Elie; C. Jacquot; F. Kiran; M. Urdaci (Microbiota in Health and Disease)
Objective: Bacteriocin production is proposed as an important factor in the beneficial effect of probiotics. The present study used encapsulation technology to improve bacteriocin-producing Pediococcus acidilactici HM-2 survivability under in vitro gastrointestinal conditions and evaluate its impact in vivo on gastrointestinal transit and gut microbiota modulation.